Myocardial damage size assessment in the zone of infarction for indicating rescue percutaneous coronary intervention - Baškot Branislav; Obradović Slobodan; Ristić-Angelkov Anđelka; Rusović Siniša; Orozović Vjekoslav; Gligić Branko; Marković Milić; Jung Robert (Vojnosanitetski Pregled, 2008)
Background. The most important predictors of subsequent patients outcome after acute myocardial infarction (AIM) are infarct size, left ventricular ejection fraction, left ventricular volumes and presence and extent of residual myocardial ischemia. All of these variables can be directly determined through scintigraphic approaches. The presence and extent of myocardial ischemia are strong predictors for fatal and nonfatal cardiac events and improve risk statification beyond the information gleaned from clinical variables. Case report. We presented a case of 66-years-old male with myocardial infarction of anteroseptal localization. Myocardial perfusion imaging (MPI) detected a large zone of residual ischemia (culprit lesion) within infarction zone. It has an important role in risk stratification after myocardial infarction, and indicates subsequent therapeutic decision making, in this case rescue percutaneous coronary intervention (PCI). After PCI we followed the therapy effect by MPI, and we found practically normal perfusion with minimal zone of defect perfusion in the apex. Conclusion. Myocardial perfusion imaging has an important role in the initial evaluation and risk stratification of patients surviving myocardial infarction. It also plays a major role in guiding subsequent therapeutic decision making, and in monitoring the benefits of these therapeutic measures.